Cloning, expression, purification, biochemical, functional and structure characterization of an endoglucanase of family GH5_4 (RfGH5_4) from Ruminococcus flavefaciens FD-1 v3 and its application in lignocellulosic biomass conversion - Gavande, Parmeshwar (My University, 2024)
The gene encoding endoglucanase, RfGH5_4 was cloned from bacterium R. flavefaciens FD-1 v3 and purified showing approx. 41 kDa of molecular mass. RfGH5_4 had maximum enzyme activity against barley β-D-glucan (665 U/mg) followed by CMC-Na (450 U/mg), lichenan (393 U/mg), xyloglucan (343 U/mg), HEC (333 U/mg) and konjac glucomannan (285 U/mg) at optimum 55℃ and pH 5.5 of 20 mM citrate phosphate buffer. It was stable in pH range, 5.0-8.0 and between, 5℃-45℃. RfGH5_4 had high Vmax and low Km against β-D-glucan (689 U/mg and 0.54 mg/mL) and CMC-Na (525 U/mg and Km of 0.58 mg/mL). 10 mM K+ increased in the enzyme activity of RfGH5_4 by 50% possibly suggesting interactions between substrate and the active-site of RfGH5_4. The time-dependent TLC analysis of CMC-Na hydrolysates by RfGH5_4 showed the presence of cellotriose, cellotetraose and other higher oligosaccharides which demonstrated its endo-acting mode. TLC, HPLC and MALDI-TOF MS analyses of hydrolysates of RfGH5_4 treated various polysaccharides showed oligosaccharides (DP2-DP12) confirming its endo-mode and multi-ligand activity on soluble substrates whereas cellobiose and cellotriose releasing processive activity on amorphous cellulose. The homology modeling analysis showed the (β/α)8-TIM barrel structure of endoglucanase, RfGH5_4. The multiple sequence alignment of RfGH5_4 showed Glu168 and Glu292 as the catalytic residues. Trp58, Arg80, His122, Asn167, Glu168, Trp179, Ala243, Tyr245, Tyr248, Glu292, Trp325 and His340 are its conserved residues. The CD analysis for secondary structure of RfGH5_4 displayed 40.8% α-helices, 13.8% β-strands and 45% random coils as deduced by CD analysis as well as PSIPRED and SOPMA servers. Molecular dynamic simulation of RfGH5_4 structure up to 100 ns at 27℃ revealed that it retained a stable conformation as an independent molecule as well as a Rf-Cellopentaose complex. The RMSD of RfGH5_4-cellopentaose complex (0.55 nm) was lower than that of RfGH5_4 (0.71 nm) which suggested its compatibility and compactness with the cellulosic ligands. The molecular docking studies of RfGH5_4 with cellulosic ligands and hemicellulosic ligands showed strong affinity with cellotetraose, cellopentaose, cellohexaose and cellodecaose, branched xyloglucan (XLLG) and glucomannan oligosaccharides. The open groove of active-site of RfGH5_4 was responsible for the multifunctionality. The barrier-like conformation of loop L2, L3 and L4 containing amino acid Trp58 at +2 subsite with cellopentaose and cellotetraose imparted the processive behaviour to RfGH5_4 by which it can consistently hydrolyse cellooligosaccharides into cellotriose and cellobiose. SAXS and DLS analysis showed monodispersed state of RfGH5_4 at 2.5 mg/mL concentration and the rattle-toy shape in the solution form. RfGH5_4 deconstructed the NaOH pre-treated lignocellulosic biomasses (Cotton Main Stalk, ptCMS, Cotton Small Branches, ptCSB), Sugarcane Bagasse, ptSBG), Sorghum durra stalk, ptSDR), Finger Millet Stalk, ptFMS and Maize Leaves, ptMZL). The maximum Total Reducing Sugar, TRS (mg/g) was observed from ptSDR (72) followed by ptFMS (62), ptSBG (38) and ptCSB (27) in a 48 h saccharification releasing cellooligosaccharides of DP2-DP11 as confirmed by TLC and MALDI-TOF MS. Moreover, synergy of endoglucanase, RfGH5_4 was also established with cellobiohydrolase, CtCBH5A and β-glucosidase, CtGH1 from Clostridium thermocellum (50:50:100 U/g) demonstrating the saccharification of ptSDR, yielding 62.0 mg/gptSDR of TRS and 28.8 mg/gptSDR of D-glucose which was further visualised through TLC analysis. These results showed that cocktail, RfGH5_4+CtCBH5A+CtGH1 is capable of hydrolysing delignified lignocellulosic biomasses as a potential cellulase toolbox for bioethanol production.
Goyal, Arun